2022
DOI: 10.1186/s12974-022-02665-x
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 5 aggravates microglia-induced neuroinflammation following ischaemic stroke by modulating the desuccinylation of Annexin-A1

Abstract: Background Microglia-induced excessive neuroinflammation plays a crucial role in the pathophysiology of multiple neurological diseases, such as ischaemic stroke. Controlling inflammatory responses is considered a promising therapeutic approach. Sirtuin 5 (SIRT5) mediates lysine desuccinylation, which is involved in various critical biological processes, but its role in ischaemic stroke remains poorly understood. This research systematically explored the function and potential mechanism of SIRT5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…First, we confirmed the cellular source and localization of SIRT5 and ANXA1 under physiological conditions and after MCAO. Consistent with our previous study, 15 double immunofluorescence staining of brain sections revealed that SIRT5 and ANXA1 were predominantly expressed in NeuN-positive neurons and Iba1-positive microglia, and an increase in SIRT5 and ANXA1 expression was observed in MCAO mice. However, there was rather poor colocalization of SIRT5 or ANXA1 with the astrocytic marker GFAP (Figures S1 and S2).…”
Section: 1supporting
confidence: 92%
See 2 more Smart Citations
“…First, we confirmed the cellular source and localization of SIRT5 and ANXA1 under physiological conditions and after MCAO. Consistent with our previous study, 15 double immunofluorescence staining of brain sections revealed that SIRT5 and ANXA1 were predominantly expressed in NeuN-positive neurons and Iba1-positive microglia, and an increase in SIRT5 and ANXA1 expression was observed in MCAO mice. However, there was rather poor colocalization of SIRT5 or ANXA1 with the astrocytic marker GFAP (Figures S1 and S2).…”
Section: 1supporting
confidence: 92%
“…Unlike other SIRTs, SIRT5 possesses weak deacetylase activity but strong protein desuccinylase activity 12–14 . We previously reported that SIRT5 interacts with and desuccinylates annexin‐A1 (ANXA1) at lysine residue 166, promoting ANXA1 nuclear translocation and suppressing its membrane accumulation and secretion by microglia, which mediates the inflammatory response and eventually aggravates ischemic stroke injury 15 . In contrast, targeting abnormal SIRT5 has a neuroprotective effect against ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these factors contribute to neuronal injury. In line with this, SIRT5 KD in the microglia of middle cerebral artery occlusion (MCAO) mouse models exerted a protective role against cerebral ischemia/reperfusion injury [ 108 ].…”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 97%
“…Conversely, SIRT5 was shown to promote neuroinflammation and its expression was indicated to increase following ischemic stroke [ 108 ] . Mechanistically, SIRT5 desuccinylates annexin A1 (ANXA1) at Lys166, which in turn leads to a decrease in its SUMOylation.…”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%